Valor nutricional de desayuno del programa Qaliwarma y su relación con el requerimiento nutricional en preescolares, Loreto 2023 - Silva Riera, Mary Naomi (2024)
The present investigation called Nutritional Value of the Breakfast of the QaliWarma Program and its Relationship with the Nutritional Requirement in Preschoolers, loreto 2023, with the Objective: to determine the nutritional value of the breakfast provided by the Qali Warma Program and its relationship with the nutritional requirement in Preschools, Loreto 2023. Materials and Methods: A descriptive correlational and cross-sectional study was developed. The sample was made up of 30 breakfast portions served for a month. The data collection technique was carried out by directly weighing the food served. Results: In energy and macronutrients for preschoolers with the only age range of 3 to 5 yearswith the different distributions, it presented (protein and carbohydrates) within what was suitable, except for lipids (below what was recommended). In micronutrients (vitamin A, Vitamin C, iron, zinc and calcium), the majority also presented an inadequate contribution. Conclusion: There is a moderate correlation between the nutritional value of breakfast from the QaliWarma program and the nutritional requirement in preschoolers, Loreto 2023.